2019
DOI: 10.11124/jbisrir-2017-003755
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of strategies and interventions aiming to assist the transition from student to newly qualified nurse: an update systematic review protocol

Abstract: Clinical support: Clinical mentorship (with an experienced mentor selected by the new graduate nurse). Clinical learning exchanges, coordinated by area based clinical educators, providing novice nurses with an opportunity to rotate through multiple patient care areas specific to their patient population. Unit based nursing preceptors trained for the role Clinical placement: Various units: medical and surgical services, neonatal and pediatric intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 49 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…The survey questions were based on the literature (Edwards et al, 2019;Melman et al, 2016;Naylor et al, 2016) and coproduced with the student partners, who were dedicated to supporting the study throughout their deployment.…”
Section: Data Collectionmentioning
confidence: 99%
“…The survey questions were based on the literature (Edwards et al, 2019;Melman et al, 2016;Naylor et al, 2016) and coproduced with the student partners, who were dedicated to supporting the study throughout their deployment.…”
Section: Data Collectionmentioning
confidence: 99%
“…By synthesizing what is known regarding barriers and facilitators for implementing NRPs, health care organizations may be able to use this synthesis to identify their own strengths and opportunities regarding readiness to implement an NRP. A preliminary search of PROSPERO, MEDLINE (PubMed), the Cochrane Database of Systematic Reviews, and JBI Evidence Synthesis (Ovid) was conducted, and 5 similar current or in-progress systematic reviews were identified, most of which looked at the effectiveness of interventions related to the NRP, or the outcomes and impact of implementing an NRP 12–15 . One systematic review protocol, published in February 2019, was located; however, the full review is not available 12 .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] One systematic review protocol, published in February 2019, was located; however, the full review is not available. 12 No similar scoping reviews were identified. Table 1 outlines these systematic review protocols and reviews and how they differ from the proposed scoping review.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations